A Mortal Complication in a Case with Mucopolysaccharidosis type I Following Hematopoietic Stem Cell Transplantation: Pulmonary Haemorrhage - Havva Yazıcı; Ebru Canda; Esra Er; Baris Malbora; Burcu Ozturk Hismi; Huseyin Onay; Serap Aksoylar; Sema Kalkan Uçar; Ferda Ozkinay; Mahmut Çoker (Galenos Publishing House, 2021)
Mucopolysaccharidosis type I (MPS I) is a lysosomal storage disease due to mutations within the gene IDUA encoding the 'α-L-iduronidase'. The clinical manifestations concern multisystemic involvement. There are two disease modifying therapies, enzyme replacement therapy and haematopoietic stem cell transplantation (HSCT). Pulmonary haemorrhage (PH) is a rare complication of HSCT and the case was presented with the reason that the related reports were few in MPS I.